Effect of Oral Zinc Sulfate on Burning Mouth Syndrome - Banik, Ruman; Shrestha, Rubina; Khatun, Shohda (Medicine Today, 2020)
Introduction: Burning Mouth Syndrome (BMS) is a common condition having a severe burning sensation in the mouth, mainly affects menopausal women and have no definitive treatment so far. The main aim of this study was to evaluate the efficacy of zinc supplement in improving the symptoms of burning mouth syndrome. Materials and Methods: 70 patients were enrolled in this study and were randomly divided in 2 groups. The patients in the intervention group received triamcinolone acetonide topical past with oral zinc sulfate therapy twice daily that continued for 3 months and the patients in the control group receivedtriamcinolone acetonide topical past only. Results: There was a significant difference (P = 0.001) in the severity of burning sensation in the two groups after the intervention. Conclusion: Zinc supplement might lessen the intensity of burning mouth syndrome in patients with zinc deficiency. Medicine Today 2020 Vol.32(1): 55-57